Visualisasi Hasil Produksi Pangan di Provinsi Nusa Tenggara Timur - Abineno, Richard Sanni; Mamulak, Natalia Magdalena R.; SinlaE, Alfry Aristo Jansen (MEANS (Media Informasi Analisa dan Sistem), 2020)
The Agriculture Office of the Province of East Nusa Tenggara (NTT) is a regional apparatus with the main task of providing services to the community in the agricultural sector, one of which is food. In the website http://distan.nttprov.go.id does not yet contain information about the results of food production in a complete and clear manner. To overcome this problem, it is necessary to build a Food Production Visualization which is expected to display a picture of food production based on production years, commodity types and production output from each district in East Nusa Tenggara Province which is easily accessible and understood by the community. The method used in this study is the method of developing the waterfall system (waterfall cycle). The graphic design displayed on this website uses ChartJS. The programming language used is PHP 7 and MySQL as a database server. The results of this study are a Web-based Visualization of Food Production in the Province of East Nusa Tenggara that contains complete and clear information and is easily accessible to all parties.